Associations with publication and assessing publication bias in dementia diagnostic test accuracy studies. (17th March 2015) - Wilson, Claire; Kerr, Daniel; Noel‐Storr, Anna; Quinn, Terence J.
Abstract : Objective: Biomarkers are of increasing interest in dementia research. Studies describing favourable accuracy of various dementia tests have influenced research, guidelines and diagnostic criteria. Publication bias is known to compromise reports on efficacy of therapeutic interventions. Traditional methods of quantifying publication bias are not suited to reviews of diagnostic tests. We aimed to describe rates and predictors of publication of dementia test accuracy studies presented at scientific meetings. Methods: We chose three exemplar scientific meetings from 2009. Two independent researchers assessed conference proceedings and selected all abstracts relating to dementia diagnostics. We recorded basic descriptors and dichotomised results as 'positive' or 'neutral'. We assessed publication status using electronic literature databases and contacting lead authors. We described univariate and multivariate predictors of publication status using logistic regression modelling. Results: From n = 2257 abstracts, we identified n = 250 (11%) abstracts relating to dementia diagnostics. The majority n = 209 (84%) reported positive results. Only 97 (39%) of these studies are published. Univariate predictors of publication status included positive result ( p = 0.042), North American or European authors ( p = 0.047), higher number of participants ( p = 0.008) and use of a 'biomarker' test ( p = 0.035). On multivariate analysis, only increasing number of participants was independently associated with publication ( p = 0.034). Conclusions: Our strategy did not prove or disprove a publication bias effect in dementia test accuracy studies. The substantial proportion of 'positive' studies may point to a downstream 'submission bias' effect on decision to submit data to meetings. Modest rate of publication of dementia test accuracy studies is concerning, and publication bias remains possible. Copyright © 2015 John Wiley & Sons, Ltd.